INCREASING THE ACTIVITY OF SCHOOL-AGED CHILDREN - Uraimov Sanjar Ruzmatovich; Shaxbazova Gulrux Orifjon's daughter (Scholar Express Journal, 2022)
This article covers a set of knowledge related to the education of school age children, as well as information on physical fitness and development.
Keywords: Hypodynamics; hypokinesia; physical training; physical development